Method for producing textile products and textile products obtained thereby

A method using titanium dioxide and a crosslinkable binder integrated between fabric yarns addresses the complexity and durability issues of existing opaque fabric production, achieving enhanced opacity and whiteness with a pleasant feel.

JP7600492B2Active Publication Date: 2024-12-17SANKO TEKSTIL ISLETMELERI SANAYI VE TICARET AS
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2021537891
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-20
Publication Date
2024-12-17
Estimated Expiration
2039-12-20

AI Technical Summary

Technical Problem

Existing methods for producing opaque white fabrics are complex, require multiple steps, and often result in fabrics that lose whiteness over time, while also potentially imparting an unpleasant aesthetic appearance.

Method used

A method involving the application of an aqueous composition containing titanium dioxide and a crosslinkable binder to fabrics, followed by heating, which allows for the integration of titanium dioxide between yarns, enhancing opacity and whiteness without affecting the fabric's feel.

Benefits of technology

The method results in fabrics with improved opacity and whiteness that maintain their properties through multiple washes, providing effective coverage of skin and underwear, while maintaining a soft and stylish texture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600492000001
    Figure 0007600492000001
  • Figure 0007600492000002
    Figure 0007600492000002
  • Figure 0007600492000003
    Figure 0007600492000003
Patent Text Reader

Abstract

The present invention relates to a manufacturing method for obtaining a white fabric with increased opacity, comprising the following steps a) to c): a) providing at least one sheet of fabric; b) treating at least a portion of said fabric with an aqueous composition comprising titanium dioxide and at least a cross-linkable binder; and c) heating the fabric obtained in step b).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of textiles, in particular to a method for producing a treated textile product and the textile product obtained thereby, the method increasing the opacity of the textile product. The present invention also relates to a composition suitable for imparting opacity to textiles and suitable for use in the above manufacturing method. [Background technology]

[0002] White clothing and white apparel are highly valued by consumers and are in high demand in the market. However, white clothing and white apparel have some drawbacks. For example, white clothing generally reveals the color of the user's skin and / or the color and shape of the user's underwear when worn. To overcome these shortcomings, thicker fabrics or yarns and / or tightly woven yarns can be used to provide fabrics and garments that are substantially opaque and not see-through. However, such a solution only allows for the production of a very limited range of garments and clothing items, for example garments that become problematic below a certain weight range.

[0003] Titanium dioxide is commonly used to impart UV-resistant, antibacterial, and self-cleaning properties to fabrics, and it is also known that opaque white garments can be obtained by applying compositions containing titanium dioxide or TiO2 to fabrics. Patent Document 1 discloses a method for producing opaque fiber fabric. According to this method, a fabric made of polyester filament yarn is impregnated with a solution consisting of 4-7% by weight of titanium dioxide and 0.1-0.5% by weight of a dispersant based on the weight of the treated fabric. The particle size of the titanium dioxide is 0.1-0.4 μm. The solution is impregnated for 20-30 minutes to allow the solution to adhere to the fabric. The treated fabric is then coated with a transparent resin whose main component is diisocyanate. US Pat. No. 5,399,433 discloses a method for preparing an opaque fabric by increasing its covering power with TiO2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] KR910006104(B1) [Patent Document 2] GB2051163A Summary of the Invention [Problem to be solved by the invention]

[0005] The manufacturing method disclosed in Patent Document 1 requires two separate steps, one step of impregnating the fabric with titanium dioxide and the second step of coating with resin, therefore the manufacturing method disclosed in Patent Document 1 is complicated and requires a long working time. Also, the resin coating over the titanium dioxide can impart an unpleasant aesthetic appearance to the fabric, and hence the garment from which it is made. Furthermore, opaque white fabrics known in the art typically lose a gradual loss in whiteness after several home washes.

[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a method for producing a fabric, particularly a white or light-colored fabric, which overcomes the above problems and allows for increased opacity. Yet another object of the present invention is to provide a manufacturing method which allows to increase the whiteness of the fabric. It is a further object of the present invention to provide a fabric that is white or light in color and that substantially conceals a user's skin or body, or alternatively, to provide a fabric that can conceal the color or shape of a user's undergarments when the user wears a garment that includes the fabric. [Means for solving the problem]

[0007] These and other objects of the invention are achieved by the manufacturing method according to claim 1, which is the subject of the present invention.

[0008] Another subject of the invention is a fabric according to claim 17. Yet another subject of the invention is a garment as claimed in claim 23, comprising the treated fabric, the aqueous composition as claimed in claim 24, and the use of said composition in a manufacturing method according to the invention as claimed in claim 26. [Brief description of the drawings]

[0009] [Figure 1A] 1 is a photograph showing an untreated sample fabric before application of the manufacturing method of the present invention. [Figure 1B] 1 is a photograph showing the treated sample fabric after application of the manufacturing method of the present invention. [Figure 2A] 1 is a 10x magnified photograph showing an untreated sample fabric before application of the manufacturing method of the present invention. [Figure 2B] 1 is a 10x magnified photograph showing the treated sample fabric after application of the manufacturing method of the present invention. [Figure 3A] 1 is a 60x magnified photograph showing an untreated sample fabric before application of the manufacturing method of the present invention. [Figure 3B] 1 is a 60x magnified photograph showing the treated sample fabric after application of the manufacturing method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the following description, features of the present invention are described with reference to exemplary embodiments. However, any feature of the present invention disclosed herein can be combined with one or more other features disclosed herein to provide further embodiments of the present invention. Such embodiments are considered to be disclosed by this application.

[0011] As mentioned above, one of the objects of the present invention is a method for producing a treated fabric, comprising the steps of: a) Prepare at least one piece of fabric; b) treating at least a portion of said fabric with an aqueous composition comprising titanium dioxide and at least a binder, preferably a cross-linkable binder; c) heating the dough obtained in step b). The manufacturing method of the present invention has the advantage that it allows for the production of fibers suitable for use in the manufacture of white garments, for example lightweight white garments. Indeed, it has been surprisingly observed that the manufacturing method of the present invention allows for increased opacity of the fabric while keeping the fibers white, soft and stylish.

[0012] In other words, the manufacturing method of the present invention can reduce the transparency of the fabric, and as a result, it has been observed that when a user wears clothing containing the fabric of the present invention, the user's skin and underwear are no longer "see-through" through the white fabric clothing. With regard to transparency, medium-thin white fabrics are not opaque enough to adequately prevent the color and shape of skin and underwear from being clearly visible. In other words, such fabrics have low covering power.

[0013] In particular, it has been observed that the titanium dioxide of the composition adheres to the yarns and fibers of the fabric, and further, when the fabric is treated according to the manufacturing method of the present invention, the titanium dioxide is observed to be located between at least some of the yarns of the fabric, for example, between the weft and warp yarns of a woven fabric, thus resulting in a decrease in transparency relative to the untreated fabric. For example, in the fabric obtained by the present invention, titanium dioxide and a binder are located in each space defined by two adjacent warp yarns and two adjacent weft yarns passing above or below the two warp yarns.

[0014] The process of the invention also has the advantage that it makes it possible to increase the whiteness and covering power of the fabric relative to untreated fabric. In an embodiment of the present invention, the fabric suitable for use is an undyed fabric.

[0015] According to the method of the present invention, an aqueous composition comprising titanium dioxide and at least a binder, preferably a crosslinkable binder, is provided to at least a portion of a substrate. In each embodiment, the binder is a compound, for example a polymer, suitable for binding the particles of titanium dioxide to the fabric and its fibers. The aqueous composition can be applied to the fabric according to techniques known in the art. For example, in embodiments, the composition is provided to the fabric by impregnation, for example by immersing the fabric in a bath containing the composition. In embodiments, the composition is provided to the fabric for thickening.

[0016] The dough provided with the aqueous composition is then heated. According to an embodiment, step c) comprises heating the fabric at a first temperature to dry it and then heating the fabric at a second temperature suitable for curing the binder polymer on the fabric, i.e. suitable for cross-linking it, which second temperature may be higher than the first temperature.

[0017] Some embodiments of the manufacturing methods of the present invention have the advantage that they can be carried out as one continuous process. For example, the manufacturing method of the present invention can be implemented as a padding process, padding being a technique known in the textile art. Generally, the padding process involves impregnating a fabric with an aqueous composition, and passing the impregnated fabric between at least two rollers such that the impregnated fabric is pressed by the two rollers to remove excess composition. The fabric is then dried and optionally cured. For example, the fabric is impregnated with the aqueous composition by padding, preferably at a temperature in the range of 10° C. to 50° C., preferably at a temperature of 20° C. to 30° C. The pH of this aqueous composition is preferably in the range of 4 to 6, more preferably in the range of 4.5 to 5.5. The fabric impregnated with the aqueous composition can then be dried and optionally cured to crosslink the binder polymer.

[0018] According to one embodiment of the method of the present invention, a fabric can be obtained in which titanium dioxide is adhered to the yarns and fibers of the fabric. In particular, it has been observed that the method of the present invention provides a fabric in which titanium dioxide and a binder are disposed between the yarns of the fabric, for example at the intersections between the weft and warp yarns of a woven fabric, thus providing an untreated fabric with increased covering power and reduced transparency. For example, in the fabric obtained by the present invention, titanium dioxide and binder are located in each space defined by two adjacent warp yarns and two adjacent weft yarns passing above or below the two warp yarns, thus reducing the transparency of the untreated fabric.

[0019] According to an embodiment, the fabric provided in step a) of the inventive manufacturing method is stretched in at least one direction (for example at least in the weft direction or at least in the warp direction), so that the fabric is stretched during the treatment with the aqueous composition according to step b) of the inventive manufacturing method, preferably also during the heating step c). For example, the fabric may be stretched during the processing steps of padding, heating and curing. It has been observed that when the fabric provided in step a) of the manufacturing method of the invention is stretched, which is stretched during the treatment with the aqueous composition, and preferably also during the heating and curing step, the spaces between the threads (e.g. between the warp and / or weft threads) increase, so that the composition can be provided in a particularly effective manner between each thread of the fabric. It has been observed that when a fabric is stretched by the manufacturing method of the present invention, a greater amount of titanium dioxide and binder is provided between the yarns of the stretched fabric as compared to the same fabric that is not stretched during processing.

[0020] In an embodiment, the fabric provided in step a) of the inventive manufacturing process is stretched in at least one direction (e.g. at least in the weft direction) by 0.5% to 75%, preferably 0.5% to 60%, more preferably 0.5% to 50% with respect to the initial dimension of said fabric, so that the fabric is stretched during the treatment with the aqueous composition according to step b) of the inventive manufacturing process, preferably also during the heating step c).

[0021] If the fabric has a high elongation at break, such as a fabric made from or including elastomeric yarns or fibers, according to embodiments the fabric is stretched 1% to 75%, preferably 5% to 60%, more preferably 10% to 50% of its initial dimension. In an embodiment, the fabric is stretched in at least the weft direction. For example, if the fabric has a low elongation at break, such as a fabric made of essentially natural yarns or fibers, according to embodiments, the fabric is stretched 0.5% to 5%, preferably 0.75% to 5%, more preferably 1% to 5% of its initial dimension (e.g., width). In embodiments, the fabric is stretched at least in the weft direction.

[0022] Drying and curing of the substrate provided with the composition has the advantage that a particularly effective and durable bonding of the titanium dioxide to the substrate is obtained, this being especially true when the binder is a crosslinkable binder. According to embodiments, the crosslinkable binder may be a self-crosslinkable binder. According to embodiments, the crosslinkable binder may be a compound that can be crosslinked using one or more crosslinking agents. Suitable crosslinking agents may be, for example, crosslinking agents containing two or more double bonds. For example, suitable self-crosslinking binders may be selected from acrylic polymers, acrylic copolymers, and acrylic derivatives. For example, suitable binders that can be crosslinked using a crosslinking agent are polyurethanes, which can be crosslinked using, for example, isocyanates.

[0023] In embodiments, it is possible to obtain a particularly strong bond of the titanium dioxide to the substrate if the binder is a crosslinkable binder. In an embodiment, the binder, preferably the crosslinkable binder, has a glass transition temperature (Tg) in the range of -30°C to 0°C, preferably -25°C to -5°C, more preferably -20°C to -8°C. If the binder, especially the crosslinked one, has a glass transition temperature in the abovementioned range, it has the advantage that a particularly soft treated fabric can be obtained. The glass transition temperature (Tg) can be measured according to ASTM E1356.

[0024] In an embodiment, the binder has a Shore A hardness of 30° Shore A or less, preferably in the range of 5° Shore A to 25° Shore A, more preferably 10° Shore A to 20° Shore A. Shore A hardness can be measured according to ASTM D2240. Binders suitable for use in the present invention are those having a glass transition temperature (Tg) in the ranges noted above and / or a hardness in the ranges noted above. As mentioned above, when the binder has a glass transition temperature (Tg) and / or Shore A hardness in the above ranges, the binder can contain titanium dioxide to obtain a particularly soft and opaque fabric, in particular the opacity of the fabric can be improved without compromising the hand of the fabric.

[0025] In embodiments, the binding agent may be selected from the following group: The group consisting of acrylic polymers, acrylic copolymers, and acrylic derivatives; For example, vinyl acrylate, styrene acrylate, butadiene acrylonitrile, carboxylated butadiene acrylonitrile, resin; Polyurethanes and polyurethane derivatives; For example, polyether polyurethane, polyester polyurethane, polycarbonate polyurethane, polyester polyether polyurethane, polyether polycarbonate polyurethane, polyester polycarbonate polyurethane, blocked isocyanates; Polyisocyanates; and A mixture of the above. In a preferred embodiment, the binder may be selected from the group consisting of butadiene acrylic copolymers, styrene acrylic copolymers, vinyl acrylate, styrene acrylate, butadiene acrylonitrile, carboxylated butadiene acrylonitrile, polyether polyurethanes, polyester polyurethanes, polycarbonate polyurethanes, polyester polyether polyurethanes, polyether polycarbonate polyurethanes, polyester polycarbonate polyurethanes, and mixtures thereof.

[0026] For example, the currently commercially available product "ORGAL ES61" (registered trademark), (Organik kimya), and the commercially available product "HELIZARIN BINDER TOW" (registered trademark), (Archroma) are suitable for use in the composition as a binder according to the invention. For example, the product EDOLAN SN (Tanatex Chemicals), a currently commercially available aliphatic polyether-based polyurethane, in combination with a crosslinker, is suitable for use in the compositions of the present invention. The suitable cross-linking agent mentioned above may be, for example, a cross-linking agent that contains two or more double bonds. For example, the currently commercially available product EDOLAN XCIB (Tanatex Chemicals) is suitable for use as a crosslinker when EDOLAN SN is used. The binder has the advantage that it contributes to the adhesion of the titanium dioxide to the substrate.

[0027] The present invention has the advantage that it allows for the production of treated fabrics that can withstand several home washes, in other words, the present invention allows for the production of treated fabrics that can be washed at home several times while maintaining substantially the same opacity and whiteness properties. In particular, it was observed that the opacity and whiteness properties of fabrics treated according to the present invention remained substantially unchanged even after 15 home launderings.

[0028] In an embodiment, the fabric may be adapted and incorporated into a garment prior to step b), for example, where an aqueous composition comprising titanium dioxide and a binder is provided to the garment by impregnation (for example, by immersion). The garment can then be heated to dry and fix the composition to the garment. In an embodiment, the amount of titanium dioxide in the aqueous composition is in the range of 0.5% to 40% by weight of the composition, preferably in the range of 5% to 30% by weight, more preferably in the range of 10% to 20% by weight. In an embodiment, the titanium dioxide has an average particle size in the range of 0.25 μm to 4 μm, preferably 0.4 μm to 3 μm, and more preferably 0.5 μm to 2 μm.

[0029] In an embodiment, the amount of binder in the composition is in the range of 0.5% to 10% by weight of said composition, preferably in the range of 2% to 8% by weight, more preferably in the range of 4% to 6% by weight. In an embodiment, the amount of binder in the aqueous composition is less than the amount of titanium dioxide in the aqueous composition. In this case, the advantage is that white-treated fabrics can be obtained which have a particularly pleasant appearance and feel.

[0030] In an embodiment, the composition may further comprise at least one polishing agent. If the aqueous composition comprises a polishing agent, it has the advantage that treated fabrics having a particularly bright white colour can be obtained. In an embodiment, the brightener is preferably a stilbene or a stilbene derivative, more preferably a triazine stilbene disulfonic acid or a derivative thereof. As an example of a polishing agent, the currently commercially available product "BLANKOPHOR B SUN" (registered trademark) (Tanatex Chemicals BV) is suitable for use in the composition according to the invention. In an embodiment, the amount of polishing agent in the composition ranges from 0.5% to 10% by weight, preferably from 1% to 8% by weight, more preferably from 2% to 5% by weight.

[0031] In embodiments, the aqueous composition may further comprise at least one dispersing agent. As used herein, the term "dispersing agent" refers to an agent suitable for inclusion in a dispersion, such as an aqueous composition, to improve separation of particles in the dispersion and prevent settling or agglomeration. In an embodiment, the amount of the dispersant ranges from 0.01% to 2% by weight of the composition, preferably from 0.1% to 1% by weight, more preferably from 0.4% to 0.6% by weight.

[0032] In an embodiment, the dispersant is selected from polyacrylates, preferably acrylic copolymers. As examples of dispersants, the currently commercially available products "DEKOL SN 100" (registered trademark) (BASF) and "SANYON DQ" are suitable for use in the compositions according to the present invention. It has been observed that the distribution of titanium dioxide on the fabric is particularly uniform when the aqueous composition contains a dispersant.

[0033] In embodiments, the aqueous composition may further comprise at least one stabilizer. As used herein, the term "stabilizer" refers to an agent that substantially prevents physical and / or chemical changes in the composition that contains it. Such stabilizers are known and are also useful as suds suppressors and / or to prevent the formation of polymeric films on padding rollers. In an embodiment, the amount of stabilizer ranges from 0.01% to 2% by weight of the composition, preferably from 0.1% to 1% by weight, more preferably from 0.2% to 0.5% by weight. In an embodiment, the stabilizer is an alkoxylate compound or a mixture of alkoxylates. As examples of stabilizers, the currently commercially available products "VITEXOL PFA" (BASF) and "HELIZARINCOMP.PFA" are suitable for use in the compositions according to the invention.

[0034] In embodiments, the aqueous composition may further comprise at least one humectant, in an amount ranging from 0.01% to 2% by weight of the composition, preferably from 0.1% to 1% by weight, more preferably from 0.2% to 0.4% by weight. In an embodiment, the wetting agent is a non-ionic wetting agent, preferably selected from the group consisting of sulfonate and phosphonate non-ionic wetting agents. As an example of a wetting agent, the currently commercially available product "COTTOCLARIN TR CT" (BRP Kimya) is suitable for use in the compositions of the present invention.

[0035] In an embodiment, the aqueous composition may further comprise at least one mineral filler different from titanium dioxide. In an embodiment, the amount of the mineral filler ranges from 0.1% to 20%, preferably from 0.5% to 10%, more preferably from 1% to 5% by weight of the composition. In an embodiment, the mineral filler may be selected from calcium carbonate, calcium sulfate, kaolin, talc, and mixtures thereof.

[0036] The method of the present invention can be carried out using any type of dough. In an embodiment, the fabric is a woven fabric, preferably a twill fabric, more preferably a denim fabric. In embodiments, the fabric may include natural fabrics, regenerated fabrics, synthetic fabrics, and mixtures thereof. In embodiments, the fabric may comprise natural and / or regenerated and / or synthetic and / or blended yarns. Natural yarns, as used herein, are yarns comprising natural fibers selected from cotton, wool, flax, kenaf, ramie, hemp, linen, and mixtures thereof. As used herein, recycled yarn is yarn comprising recycled fibers, which may be selected, for example, from viscose, modal, tencel, and mixtures thereof.

[0037] As used herein, synthetic yarn is yarn comprising synthetic fibers which may be selected from polyester, nylon, polyurethane, spandex (elastane), acrylic, modacrylic, acetate, polyolefin, vinyl, and mixtures thereof. As used herein, a blended yarn is a yarn that includes at least two types of yarn: natural yarn (eg, cotton), regenerated yarn, and yarn of synthetic fibers.

[0038] As mentioned above, in an embodiment, step c) of the manufacturing method of the present invention comprises heating the fabric provided with an aqueous composition comprising titanium dioxide and at least one binder at a first temperature to dry the fabric, and then and drying the substrate at a second temperature to harden the substrate, i.e., to crosslink the binder applied to the substrate. In an embodiment, the first temperature is in the range of 90° C. to 200° C., preferably 100° C. to 160° C., and more preferably 110° C. to 150° C. In an embodiment, the second temperature is in the range of 150° C. to 200° C., and preferably 160° C. to 180° C. As described above, in an embodiment, the second temperature is higher than the first temperature. The manufacturing method according to the present invention has the advantage that it is particularly fast and easy to carry out, for example, in an embodiment, the treatment time of step b) of treating the fabric with the aqueous composition comprising titanium dioxide and a binder is in the range of 0.1 to 60 seconds, preferably 0.5 to 30 seconds, more preferably 1 to 10 seconds. For example, in an embodiment, the processing time for the step of hardening the dry fabric is in the range of 15 seconds to 90 seconds, and preferably in the range of 30 seconds to 60 seconds.

[0039] Another subject of the invention is a fabric obtainable by the process according to the invention, i.e. a fabric treated according to the process which increases the opacity of the fabric. As mentioned above, in the fabric obtained by the present invention, it has been observed that titanium dioxide adheres to the yarns and fibers of the fabric. It has also been observed that in the fabric obtained by the present invention, titanium dioxide is also located between the yarns of the fabric, i.e., at the intersections between the weft and warp yarns of the woven fabric. This leads to a decrease in transparency, i.e., an increase in covering power, compared to the untreated fabric.

[0040] For example, in the fabric obtained by the present invention, titanium dioxide and a binder are located in each space defined by two adjacent warp yarns and two adjacent weft yarns passing above or below the two warp yarns. In an embodiment, the fabric is a woven fabric comprising weft and warp threads woven together, and at least a portion of said titanium dioxide is located at the intersection between said weft and warp threads. That is, the titanium dioxide-containing binder is held within each space bounded by two adjacent warp threads and two adjacent weft threads passing above or below said two warp threads. The presence of titanium dioxide in these locations significantly improves opacity (or covering power) without the need for low Ne (English cotton count) yarns (i.e. high linear density yarns). According to an embodiment, the fabric may be a twill weave, preferably a denim fabric.

[0041] The relative amount of titanium dioxide disposed between the yarns of a fabric, e.g., between the warp and weft yarns, has been observed to vary depending on the fabric construction and / or depending on the stretching of the fabric during the method of manufacture of the fabric. For example, as the density of the warp yarns increases, the relative amounts of titanium dioxide and binder between the warp yarns decreases. For example, a fabric that is stretched during the manufacturing process of the present invention will have an increased relative amount of titanium dioxide and binder between the warp yarns of the fabric compared to the same fabric that is stretched less or not at all during manufacturing.

[0042] The terms "treated fabric" and "final fabric" refer to the fabric obtained by the process of the present invention, i.e. the fabric used for garments. Thus, the following fabric characteristics and properties refer to the dry, final, processed fabric as found in the garment. According to an embodiment, in the treated substrate, the titanium dioxide has an average particle size in the range of 0.25 μm to 4 μm, preferably 0.4 μm to 3 μm, more preferably 0.5 μm to 2 μm. According to an embodiment, in the final treated fabric, the amount of titanium dioxide is in the range of 3% to 10% by weight of the total weight of the treated fabric, preferably in the range of 6% to 8% by weight of the total weight of the treated fabric, i.e. the treated and dried fabric.

[0043] In an embodiment, the amount of titanium dioxide in the aqueous composition is selected to obtain a final treated fabric in which the amount of titanium dioxide is in the range of 3% to 10% by weight of the total weight of the fabric, preferably in the range of 6% to 8% by weight of the total weight of the fabric. In an embodiment, in the final treated fabric, e.g., fabric incorporated into a garment, the amount of binder is in the range of 0.5% to 4% by weight of the total weight of the treated fabric, preferably in the range of 2% to 3.5% by weight of the total weight of the treated fabric. In an embodiment, the amount of binder in the aqueous composition may be selected such that in the treated fabric, the amount of binder is in the range of 0.5% to 4% by weight based on the total weight of the fabric, preferably in the range of 2% to 3.5% by weight of the total weight of the fabric.

[0044] According to the embodiment, the amount of binder in the fabric is less than the amount of titanium dioxide in the fabric. In this case, as described above, it is advantageous to obtain a white treated fabric having a particularly pleasant appearance and feel. For example, the treated fabric of the invention contains titanium dioxide in an amount ranging from 5% to 10% by weight, preferably from 6% to 8% by weight, of the total weight of the treated fabric, and a binder in an amount ranging from 1% to 5% by weight, preferably from 2% to 4% by weight, of the total weight of the treated fabric. The final fabric treated according to the invention has the advantage that it is wash resistant, in particular the opacity and whiteness of the fabric are not substantially affected or diminished even after several home washes.

[0045] Opacity and whiteness can be measured according to known methods, for example by using spectrophotometry. As used herein, the term "opacity" refers to the covering power of a fabric (i.e., the quality of the fabric that makes it difficult to see through). For example, the more opaque a fabric is, the less visible it is through the fabric. In other words, the more opaque a fabric is, i.e., the more opaque it is, the more it can prevent what is underneath it from being exposed through the fabric.

[0046] In an embodiment, the binder has a glass transition temperature (Tg) in the range of −30° C. to 0° C., preferably −25° C. to −5° C., more preferably −20° C. to −8° C., with the advantage that a particularly soft treated fabric is obtained. The glass transition temperature (Tg) can be measured according to ASTM E1356. According to an embodiment, the binder may have a Shore A hardness ≦30° Shore A, preferably in the range of 5° Shore A to 25° Shore A, more preferably in the range of 10° Shore A to 20° Shore A. Shore A hardness can be measured according to ASTM D2240.

[0047] As mentioned above, when the binder has a glass transition temperature (Tg) and / or Shore A hardness in the above ranges it is possible to obtain particularly soft opaque textures. According to an embodiment, the fabric of the present invention may optionally comprise, in addition to titanium dioxide and at least one binder, one or more gloss agents, and / or one or more dispersants, and / or one or more stabilizers, and / or one or more wetting agents.

[0048] In an embodiment, the final treated substrate may contain a polishing agent in an amount ranging from 0.5% to 3% by weight, preferably from 1% to 2% by weight, based on the total weight of the treated substrate. In an embodiment, the amount of polishing agent in the aqueous composition may be selected to obtain a substrate in the range of 0.5% to 3% by weight, preferably from 1% to 2% by weight, based on the total weight of the treated substrate. In an embodiment, the fabric may include a dispersant in an amount ranging from 0.1% to 1% by weight, preferably from 0.2% to 0.5% by weight of the total weight of the treated fabric. In an embodiment, the amount of dispersant in the aqueous composition may be selected to obtain a fabric having an amount of dispersant in the range of 0.1% to 1% by weight, preferably 0.2% to 0.5% by weight, of the total weight of the treated fabric.

[0049] In an embodiment, the fabric of the present invention may comprise a stabilizer in an amount ranging from 0.1% to 0.5% by weight, preferably from 0.2% to 0.4% by weight of the total weight of the treated fabric. In an embodiment, the amount of stabilizer in the aqueous composition may be selected such that the amount of stabilizer is in the range of 0.1% to 0.5% by weight, preferably from 0.2% to 0.4% by weight of the total weight of the treated fabric. In an embodiment, the fabric of the present invention may comprise a wetting agent in an amount ranging from 0.05% to 0.5% by weight, preferably from 0.1% to 0.4% by weight of the total weight of the treated fabric. In an embodiment, the amount of wetting agent in the aqueous composition may be selected to obtain a treated fabric in which the amount of wetting agent is in the range of 0.05% to 0.5% by weight, preferably in the range of 0.1% to 0.4% by weight of the total weight of the fabric.

[0050] The compositions on the substrate of the present invention can be analyzed according to known methods to determine the amounts of various components present in the dried and cured composition. For example, titanium dioxide can be extracted from the treated substrate, separated and decomposed according to known methods, and characterized according to the test ASTM D1394 - Chemical Analysis of White Titanium Pigment. According to one aspect of the invention, the fabric of the invention is suitable for fitting into a garment. A further subject of the invention is a garment comprising the fabric obtained according to the invention. The fabric treated according to the invention has the advantage that the user's skin is (partially) invisible through the fabric. Similarly, the underwear of the user worn under the garment according to the invention has the advantage that it is not visible through said garment.

[0051] A further subject of the present invention is an aqueous composition for the treatment of fibers, i.e. fabrics, preferably textiles, The aqueous composition comprises titanium dioxide and at least one binder, preferably a crosslinkable binder; the titanium dioxide is in an amount in the range of 5 to 500 g / L, preferably in the range of 50 to 400 g / L, more preferably in the range of 75 to 300 g / L, and even more preferably in the range of 90 to 200 g / L; The binder is present in an amount in the range of 1 to 100 g / L, preferably in the range of 10 to 80 g / L, more preferably in the range of 30 to 70 g / L, and even more preferably in the range of 35 to 60 g / L. According to an embodiment, the aqueous composition comprises titanium dioxide and at least one binder, preferably a crosslinkable binder, the titanium dioxide is in an amount ranging from 0.5% to 40% by weight of the composition, preferably in the range of 5% to 30% by weight, more preferably in the range of 10% to 20% by weight; The binder is present in an amount in the range of 0.5% to 10% by weight of the composition, preferably in the range of 2% to 8% by weight, more preferably in the range of 4% to 6% by weight.

[0052] The aqueous compositions that are the subject of the present invention are suitable for use in the process of the present invention. Thus, the features of the aqueous compositions disclosed herein with respect to the composition in the process of the present invention are intended to be used for the composition itself, and vice versa. That is, the features disclosed herein with respect to the aqueous composition itself are intended to be used for the composition in the process of the present invention. The aqueous composition can be prepared by known methods. For example, it can be advantageously prepared by mixing different components. According to an embodiment, the components can be provided and mixed together to obtain the aqueous composition. According to an embodiment, two or more components can be provided successively during mixing.

[0053] According to an embodiment, the aqueous composition may have a pH in the range of 4 to 6, preferably in the range of 4.5 to 5. According to an embodiment, the aqueous composition may further comprise at least one polishing agent in an amount in the range of 0.5% to 10%, preferably 1% to 8%, more preferably 2% to 5% by weight of said composition.

[0054] According to an embodiment, the aqueous composition comprises: Titanium dioxide at 5 to 500 g / L; It may contain 1 to 100 g / L of at least one binder. According to an embodiment, the concentration of titanium dioxide in the aqueous composition ranges from 50 to 400 g / L, preferably from 75 to 300 g / L, more preferably from 90 to 200 g / L. According to an embodiment, the concentration of the binder in the aqueous composition ranges from 10 to 80 g / L, preferably from 30 to 70 g / L, more preferably from 35 to 60 g / L. According to an embodiment, the aqueous composition may further comprise one or more brighteners, the concentration of which in the aqueous composition is in the range of 5 to 40 g / L, preferably 10 to 35 g / L, more preferably 15 to 30 g / L.

[0055] According to an embodiment, the aqueous composition may further comprise one or more dispersants, the concentration of the dispersant in the aqueous composition being in the range of 1 to 20 g / L, preferably 2.5 to 10 g / L, more preferably 4 to 6 g / L. According to an embodiment, the aqueous composition may further comprise one or more stabilizers, the concentration of which in the aqueous composition is in the range of 1 to 10 g / L, preferably 2 to 6 g / L, more preferably 3 to 5 g / L. According to an embodiment, the aqueous composition may further comprise one or more wetting agents, the concentration of which in the aqueous composition is in the range of 0.5 g / L to 10 g / L, preferably 1 to 5 g / L, more preferably 2 to 4 g / L.

[0056] According to an embodiment, the aqueous composition may further comprise one or more mineral fillers different from titanium dioxide. According to an embodiment, the concentration of the mineral fillers different from titanium dioxide in the aqueous composition ranges from 10 to 100 g / L, preferably from 10 to 50 g / L of at least one mineral filler. According to an embodiment, the mineral fillers may be selected from the group consisting of calcium carbonate, calcium sulfate, kaolin, talc, and mixtures thereof.

[0057] The subject of the present invention is also the use of the composition according to the invention in the manufacturing process according to the invention. The present invention has the advantage that a white fabric with high opacity can be obtained in a simpler, faster and cheaper manner compared to the manufacturing methods known in the art.

[0058] Experimental Section Example 1 - Composition Example 1 relates to different embodiments of the aqueous composition of the present invention. In all exemplary compositions, the final volume of the aqueous composition is 1L. Composition 1: Titanium dioxide 100g / L ORGAL ES61(registered trademark) 40g / L Water to final volume of 1L Composition 2: Titanium dioxide 100g / L ORGAL ES61 (registered trademark) 40g / L SANYON DQ 5g / L HELIZARIN COMP. PFA 4g / L BLANKOPHOR BSUN (registered trademark) 20g / L COTTOCLARIN TR CT 3g / L Water to final volume of 1L Composition 3: Titanium dioxide 100g / L ORGAL ES61 (registered trademark) 40g / L SANYON DQ 5g / L HELIZARIN COMP. PFA 4g / L COTTOCLARIN TR CT 3g / L Water to final volume of 1L

[0059] In the above compositions 1-3, ORGAL ES61® (a styrene-acrylic copolymer with a Tg of −12° C.) was the binder, SANYONDQ was the dispersant, HELIZARIN COMP. PFA was the stabilizer, BLANKOPHOR BSUN® was the gloss agent, and COTTOCLARIN TRCT was the wetting agent.

[0060] Composition 4: Titanium dioxide: 100g / L HELIZARIN COMP. PFA: 46g / L SANYON DQ: 5g / L HELIZARIN COMP. PFA: 4g / L COTTOCLARIN TR CT: 3g / L Water: to final volume of 1L Composition 5: Titanium dioxide: 100g / L HELIZARIN BINDER TOW: 46g / L SANYON DQ: 5g / L HELIZARIN COMP. PFA: 4g / L BLANKOPHOR BSUN: (Registered Trademark) 20g / L COTTOCLARIN TR CT: 3g / L Water: to final volume of 1L

[0061] In the above compositions 4-5, HELIZARIN COMP. PFA (an acrylic copolymer having a Tg of -18°C) was the binder, SANYON DQ was the dispersant, HELIZARIN COMP. PFA was the stabilizer, BLANKOPHOR (registered trademark) BSUN was the gloss agent, and COTTOCLARIN TRCT was the wetting agent.

[0062] Composition 6: Titanium dioxide: 100g / L EDOLAN SN: 30g / L EDOLAN XCIB: 5g / L SANYON DQ: 5g / L HELIZARIN COMP. PFA: 4g / L COTTOCLARIN TR CT: 3g / L Water: to final volume of 1L Composition 7: EDOLAN SN: 30G / L EDOLAN XCIB: 5G / L SANYON DQ: 5G / L HELIZARIN COMP. PFA: 4G / L BLANKOPHOR B-SUN: (registered trademark) 20g / L COTTOCLARIN TR CT: 3g / L Water: to final volume of 1L

[0063] In the above compositions 6-7, EDOLAN SN (aliphatic polyether-based polyurethane) was the binder, EDOLAN XCIB was the crosslinker, SANYON DQ was the dispersant, HELIZARIN COMP. PFA was the stabilizer, BLANKOPHOR BSUN® was the gloss agent, and COTTOCLARIN TRCT was the wetting agent. The Shore A hardness of the bonding agent EDOLANSN crosslinked with the crosslinking agent EDOLANXCIB is 20° Shore A.

[0064] All of the above compositions 1 to 7 can be prepared by mixing and stirring the components (eg, for about 30 minutes) to obtain a homogenous mixture.

[0065] Example 2 Production of treated fabric Treated fabric 1 The cotton fabric was treated with "Composition 1" according to Example 1. In the padding an aqueous composition was used. The fabric was dried at 150°C and cured at 180°C for 45 seconds. The resulting treated fabric contained the following: Titanium dioxide approx. 7% by weight Binder: approx. 2.8% by weight These amounts are expressed as a weight percentage based on the total weight of the treated fabric.

[0066] Treated fabric 2 The cotton fabric was treated with "Composition 3" according to Example 1. An aqueous composition was used in the padding. The fabric was dried at 150°C and cured at 180°C for 45 seconds. The resulting treated fabric contained the following: Titanium dioxide approx. 7% by weight Binder: approx. 2.8% by weight Dispersant: approx. 0.35% by weight Stabilizer: Approximately 0.28% by weight Wetting agent: approx. 0.2% by weight These amounts are expressed as a weight percentage based on the total weight of the treated fabric.

[0067] Treated fabric 3 The cotton fabric was treated with "Composition 4" according to Example 1. An aqueous composition was used in the padding. The fabric was dried at 150°C and cured at 180°C for 45 seconds. The resulting treated fabric contained the following: Titanium dioxide approx. 7% by weight Binder: approx. 3.22% by weight Dispersant: approx. 0.35% by weight Stabilizer: Approximately 0.28% by weight Wetting agent: approx. 0.2% by weight These amounts are expressed as a weight percentage based on the total weight of the treated fabric.

[0068] Treated fabrics 4 The cotton fabric was treated with "Composition 6" according to Example 1. An aqueous composition was used in the padding. The fabric was dried at 150°C and cured at 180°C for 45 seconds. The resulting treated fabric contained the following: Titanium dioxide approx. 7% by weight Binder: approx. 2.1% by weight Crosslinking agent: approx. 0.35% by weight Dispersant: approx. 0.35% by weight Stabilizer: Approximately 0.28% by weight Wetting agent: approx. 0.2% by weight These amounts are expressed as a weight percentage based on the total weight of the treated fabric.

[0069] Example 3 Opacity and CMC DE (Color Difference) Evaluation of Exemplary Treated Fabrics The opacity and CMC DE (color difference) of three samples of the fabric before and after the manufacturing method of the present invention were measured. In particular, the fabrics were treated according to Example 2 to obtain "treated fabric 1", "treated fabric 3" and "treated fabric 4". The opacity and CMC DE (colour difference) were measured spectrophotometrically according to methods known per se by a Datacolor 600 spectrophotometer using white and black background cards. The opacity of the fabric was measured on the backing paper as a ratio expressed as a percentage of the light reflectance R0 of a single sheet to the intrinsic light reflectance R∞ of the same sample according to the following formula: Opacity=100×R0 / R∞

[0070] The single sheet light reflectance coefficient "R0" is defined as the light reflectance coefficient of a single sheet of fabric with a black cavity as a backing. The intrinsic light reflectance "R∞" is defined as the light reflectance of a layer or pad of fabric having a thickness such that the measured reflectance does not change with further increase in the thickness of the layer or pad. In this case, the thickness of the layer or pad corresponds to the thickness of a piece of fabric, since a piece of fabric is a piece of fabric when unfolded. To increase the thickness of the layers or pads to be analyzed, the thickness of these layers or pads can be increased to a thickness where the reflectance value does not change with further increase in thickness. For example, this can be done by folding the fabric so that two or more pieces of the same fabric overlap.

[0071] "CMC DE" is the difference between the sample color and the reference color. CMC DE was measured with a Datacolor600 spectrophotometer using white and black background cards. First, the fabric was placed on a white background and the reflectance was measured using the Datacolor600 spectrophotometer. Then, the same fabric was placed on a black background and the reflectance was measured using the Datacolor600 as a sample. The color difference (CMC DE) between the fabric on a white background and the fabric on a black background was determined spectrophotometrically according to known methods. The smaller the value of CMC DE, the more opaque the fabric. In other words, the more opaque the fabric, the smaller the color difference between white and black.

[0072] The following results were obtained: Untreated fabric CMC DE:3.17 Opacity: 87% Fabric 1 treated according to Example 2 CMC DE: 1.84 Opacity: 95% Fabric 3 treated according to Example 2 CMC DE: 1.90 Opacity: 95.8% Fabric 4 treated according to Example 2 CMC DE: 1.91 Opacity: 95.32%

[0073] In the case of "treated fabric 1", it was observed that the manufacturing method of the present invention increases the opacity of the fabric by about 8% with respect to the untreated fabric. The manufacturing method of the present invention also makes it possible to reduce the CMC DE (i.e. color difference) by about 42% with respect to the untreated fabric. In the case of "treated fabric 3", the manufacturing method of the present invention makes it possible to increase the opacity of the fabric by about 8.8% with respect to the untreated fabric. The manufacturing method of the present invention also makes it possible to reduce the CMC DE (i.e. color difference) by about 40% with respect to the untreated fabric. In the case of "treated fabric 4", the manufacturing method of the invention makes it possible to increase the opacity of the fabric by about 8.3% compared to the untreated fabric, and also makes it possible to reduce the CMC DE (i.e. color difference) by about 39.7% with respect to the untreated fabric.

[0074] The results obtained with the manufacturing method of the present invention can also be observed in the attached figures, which show sample fabrics at different magnifications before and after treatment with the manufacturing method of the present invention. In particular, Figures 1A and 1B are photographs showing a sample fabric before (Figure 1A) and after (Figure 1B) treatment according to the manufacturing method of the present invention. 2A and 2B are photographs taken at a magnification of 10x, and FIGS. 3A and 3B are photographs taken at a magnification of 60x. For example, as can be seen from Figures 1A and 1B, and Figures 2A and 2B, the treated fabric treated with the method of the present invention has improved opacity and whiteness relative to the untreated fabric.

[0075] In Figure 3B, titanium dioxide particles can be seen among the fibers and yarns of the treated fabric, which are not visible in Figure 3A, which shows the untreated fabric. 3A and 3B show that the present invention is effective in providing titanium dioxide to a fabric.

Claims

1. 1. A method for producing a dough, comprising: a) providing at least one piece of fabric; b) treating at least a portion of the fabric with an aqueous composition comprising titanium dioxide and at least a binder; and c) heating the dough obtained in step b), The method for producing a dough, wherein the binder has a glass transition temperature (Tg) in the range of -30°C to 0°C and / or a Shore A hardness of 30° Shore A or less.

2. In claim 1, wherein step c) comprises heating the dough at a first temperature to dry the dough and then heating the dough at a second temperature to crosslink the binder on the dough, the second temperature being greater than the first temperature.

3. In any one of claims 1 or 2, 13. A method for producing a dough, characterized in that the dough provided in step a) is stretched in at least one direction, such that the dough is in a stretched state during treatment with the aqueous composition according to step b).

4. In claim 3, 13. A method for producing a fabric, characterized in that the fabric provided in step a) is stretched between 0.5% and 75% in at least the weft direction with respect to an initial dimension of the fabric.

5. In any one of claims 1 to 4, 2. A method for producing a dough, characterized in that the aqueous composition in step b) is provided to the dough by padding.

6. In any one of claims 1 to 5, The method for producing a fabric, wherein the binder is selected from the group consisting of acrylic polymers, acrylic copolymers and derivatives, polyurethanes and derivatives, blocked isocyanates, polyisocyanates, and mixtures thereof.

7. In any one of claims 1 to 6, The method for producing a dough, wherein the binder has a glass transition temperature (Tg) in the range of -25°C to -5°C.

8. In any one of claims 1 to 7, The method for producing a dough, wherein the binder has a Shore A hardness in the range of 5° Shore A to 25° Shore A.

9. In any one of claims 1 to 8, The method of manufacturing a fabric, characterized in that the fabric is incorporated into a garment prior to step b).

10. In any one of claims 1 to 9, The method for producing a dough, wherein the titanium dioxide in the composition is in the range of 5 to 500 g / L.

11. In any one of claims 1 to 10, The method for producing a dough, wherein the titanium dioxide has an average particle size in the range of 0.25 μm to 4 μm.

12. In any one of claims 1 to 11, A method for producing dough, characterized in that the binder in the composition is in the range of 1 to 100 g / L.

13. In any one of claims 1 to 12, The composition further comprises at least one glaze.

14. In claim 13, A method for producing a fabric, characterized in that the amount of the gloss agent in the composition is in the range of 5 to 40 g / L.

15. In any one of claims 2 to 14, A method for producing dough, wherein the first temperature is in the range of 90°C to 200°C.

16. In any one of claims 2 to 15, A method for producing dough, wherein the second temperature is in the range of 150°C to 200°C.

17. A dough obtained by the method according to any one of claims 1 to 16.

18. In claim 17, The fabric is a woven fabric including weft and warp yarns woven together, and at least a portion of the titanium dioxide and binder is located within each space defined by two adjacent warp yarns and two adjacent weft yarns passing above or below the two warp yarns.

19. In claim 18, The fabric is a twill fabric.

20. In any one of claims 17 to 19, The titanium dioxide has an average particle size in the range of 0.25 μm to 4 μm.

21. In any one of claims 17 to 20, The amount of titanium dioxide is in the range of 3% to 10% by weight of the total weight of the fabric.

22. In any one of claims 17 to 21, The amount of the binder is in the range of 0.5% to 4% by weight of the dough.

23. A garment comprising the fabric according to any one of claims 17 to 22.

24. 1. An aqueous composition for treating textiles, comprising: Titanium dioxide and at least one binder; The titanium dioxide is in the range of 5 to 500 g / L, the binder is in an amount ranging from 1 to 100 g / L; The aqueous composition, wherein the binder has a glass transition temperature (Tg) in the range of -30°C to 0°C and / or a Shore A hardness of 30° Shore A or less.

25. 25. The aqueous composition of claim 24, Further comprising at least one gloss agent; The aqueous composition is characterized in that the brightening agent is present in an amount ranging from 5 to 40 g / L.

26. In the method for producing the fabric according to any one of claims 1 to 16, A method for producing a dough, comprising using the aqueous composition according to claim 24 or 25.

Citation Information

Patent Citations

  • A thermal reflective coating cloth

    CN105755800A

  • Infrared reflective coating compositions

    EP2452986A1

  • Coating compositions

    GB1391593A

  • Opacified Polyester Textile Material

    GB2051163A

  • Producing white synthetic yarn

    GB2063929A